Model Pendidikan Spiritual dan Akhlak Di Sekolah - Riza Awal Novanto (AL-MUFASSIR, 2021)
Writing this journal is intended to determine the model of spiritual and moral education in schools. Spiritual education is a basic human nature, so it is very important to shape human morals. Spiritual education aims to strengthen the soul and spirit in order to maintain a good relationship with Him. So that it makes human life more meaningful. While morality is the result of spiritual education. Moral education is education that seeks to introduce, instill and appreciate the patterns, attitudes and actions of humans related to God, humans and their environment. Thus, spiritual and moral education is very important to be applied in schools in an effort to reawaken humans in this case are students on the straight path to human nature. Therefore, a model of spiritual and moral education is needed to achieve this goal. The model in spiritual and moral education is divided into four, namely: First, religious views. Second, the educational process. Third, curricular. Fourth, operational strategy.